A Two-Fold Authentication Mechanism for Network Security - Selvamani, D.; Selvi, V. (Asian Journal of Engineering and Applied Technology, 2018)
Security is very important90 for any kind of networks. As a main communication mode, the security mechanism for multicast is not only the measure to ensure secured communications, but also the precondition for other security services. Attacks are one of the biggest concerns for security professionals. Attackers usually gain access to a large number of computers by exploiting their vulnerabilities to set up attack armies. This paper presents a double way authentication mechanism which uses the functionality of Elliptical Curve Cryptography, Kerberos System and RSA algorithm. ECC algorithm utilized to encrypt the user information whereas RSA used to encrypt the secret key itself to ensure the more security in the networks.